Functional hypogonadism in middle-aged and older men: testosterone treatment or not?. Issue 3 (3rd August 2021) - Grossmann, Mathis; Jones, Thomas Hugh
Abstract : Clinicians commonly encounter middle-aged and older men who present with functional hypogonadism, that is, with clinical features compatible with androgen deficiency and lowered serum testosterone, but without evidence of organic hypothalamic-pituitary-testicular axis pathology. Whether, and when, testosterone therapy should be offered to such men remains uncertain and controversial, in part due to the lack of definitive evidence regarding long-term patient-important health outcomes with testosterone treatment. In this debate, we address this controversy and provide two opposing points of view on the role of testosterone treatment in older men with functional hypogonadism.